EFFORTS TO INCREASE TEACHER COMPETENCY IN TEACHING THROUGH THE USE OF THE MERDEKA TEACHING PLATFORM AT SDN PAKIS V SURABAYA ACADEMIC YEAR 2022/2023 - Irwan Muhanik (LPPM STAI Muhammadiyah Probolinggo, 2023)
The implementation of the Independent Learning Curriculum is a major change in the education system in Indonesia. These changes not only affect classroom teaching methods, but also affect school structure and management systems. In this context, the role of the school principal becomes very important, especially in supervising the curriculum implementation process. Principal supervision is very important in implementing the Independent Learning Curriculum for several reasons. Supervising the implementation of the Independent Learning Curriculum is not an easy task. A good understanding of this curriculum is required, as well as skills in supervision and school management. Therefore, it is important for school principals to continue to improve their competence in this matter. This research was conducted using the school action research method which lasted for 2 cycles. Each cycle consists of planning, implementation, observation and reflection stages. The research method used by researchers is to carry out academic supervision which includes traditional supervision and clinical supervision with subj. 10 Class teachers and fields of study The results of this research show that the implementation of the use of good practices in PMM through academic supervision in cycle 2 in the learning category is very good with a score of 4.2. With the results above, the implementation of the use of good practices in PMM through academic supervision is considered successful because the results are good and in accordance with the predetermined indicators of success in increasing teacher professionalism.